The Development of Problem-Based Learning (PBL)-Based Student Activity Sheets to Improve Problem-Solving Skills in the Topic of Reaction Rates in Phase F - Nadia Sri Febriani; Rusmini Rusmini (UNIB Press, 2026)
This study aims to describe the feasibility of developing Problem-Based Learning (PBL)-based Worksheet to improve problem-solving skills in Phase F reaction rate material, as evaluated based on validity, practicality, and effectiveness. The research design employed is Research and Development (R&D) using Thiagarajan’s 4D development model, comprising define, design, develop, and disseminate. This study is limited to the development stage and involves a pilot test. The research subject consists of PBL-based LAPDs on reaction rate material, which were pilot-tested with students in Class XI-8 at State High School 16 Surabaya. Data sources were obtained from analysis sheets, validation, activity observations, response questionnaires, as well as pretest and posttest skill assessments. Data collection techniques for this study included questionnaires, observations, and pretest-posttest skill assessments. The results of the study indicate that the PBL-based LAPD met the validity criteria, with a content validity mode score of 4 (good category) and a construct validity mode score of 4 (good category). Practicality was assessed based on the results of the student response questionnaire with a percentage of 96.1% and supported by the results of student activity observations with a percentage of 99.7%. Effectiveness was assessed based on the improvement in students’ problem-solving skills, with an overall N-gain score of 0.71 in the high (high-g) category. in the Paired Sample T-test, a p-value of 0.01 (<0.05) was obtained, so it can be concluded that there is a significant improvement in students’ problem-solving skills using PBL-based LAPD. Based on the research results obtained, it can be concluded that PBL-based LAPD on phase F reaction rate material is suitable for use in the learning process and improves problem-solving skills.